2001
DOI: 10.1172/jci12902
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbated vein graft arteriosclerosis in protein kinase Cδ–null mice

Abstract: Smooth muscle cell (SMC) accumulation is a key event in the development of atherosclerosis, including vein bypass graft arteriosclerosis. Because members of the protein kinase C (PKC) family signal cells to undergo proliferation, differentiation, or apoptosis, we generated PKCdelta knockout mice and performed vein bypass grafts on these animals. PKCdelta(-/-) mice developed normally and were fertile. Vein segments from PKCdelta(-/-) mice isografted to carotid arteries of recipient mice of either genotype led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 39 publications
(53 reference statements)
9
105
1
Order By: Relevance
“…Meanwhile, to further verify that IL-37 suppresses SMC apoptosis, we next pretreated HASMCs with exogenous IL-37 or silenced endogenous IL-37 using IL-37 small interfering RNA (siRNA; siIL-37) before we administered positive stimulation. The HASMCs were then cultured with or without hydrogen peroxide (H 2 O 2 ) or the pro-inflammatory cytokines IFN-γ and TNF-α, which are potent inducers of apoptosis [27]. As expected, flow cytometric analysis showed that treatment with H 2 O 2 or IFN-γ and TNF-α increased the frequency of apoptotic SMCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, to further verify that IL-37 suppresses SMC apoptosis, we next pretreated HASMCs with exogenous IL-37 or silenced endogenous IL-37 using IL-37 small interfering RNA (siRNA; siIL-37) before we administered positive stimulation. The HASMCs were then cultured with or without hydrogen peroxide (H 2 O 2 ) or the pro-inflammatory cytokines IFN-γ and TNF-α, which are potent inducers of apoptosis [27]. As expected, flow cytometric analysis showed that treatment with H 2 O 2 or IFN-γ and TNF-α increased the frequency of apoptotic SMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Cell apoptosis was monitored using FACS analysis with a Flow cytometric apoptosis analysis Kit (eBioscience, Annexin V-FITC and Propidium Iodide staining) [27]. …”
Section: Methodsmentioning
confidence: 99%
“…These studies also showed that PKCβII was involved in vascular smooth muscle cell activation in part through ERK and EGR-1 [59]. Leitges et al [60] showed that PKC δ-null mice showed reduced arteriosclerosis as compared with the wild-type littermates in a vein graft model. The mechanisms responsible for this are unclear because vascular smooth muscle cells from aortas of PKCδ -/-mice were significantly more resistant to apoptosis (induced by multiple stimuli) compared with controls, whereas mitogenic potential was unchanged [60].…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 94%
“…Leitges et al [60] showed that PKC δ-null mice showed reduced arteriosclerosis as compared with the wild-type littermates in a vein graft model. The mechanisms responsible for this are unclear because vascular smooth muscle cells from aortas of PKCδ -/-mice were significantly more resistant to apoptosis (induced by multiple stimuli) compared with controls, whereas mitogenic potential was unchanged [60]. Generation of tissue-specific PKC knockout models will be important in furthering our understanding of the role of PKC in vascular disease [61] and broadening our focus to include inflammatory cells as well as endothelial and smooth muscle cells.…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 99%
“…To complicate this issue, the experimental literature has been diluted with an interchanging of terms, often substituting atherosclerotic terminology for what is more identifiable as neointimal formation, either without an atherogenic stimulus 42 or with superimposed atherogenesis. 51,52 This confusion in the literature is a major obstacle to understanding the fundamental mechanisms underlying vein graft pathologies. A better appreciation of the distinction between these pathologies would use the stable development of neointima that then progresses to atherosclerotic lesion presence, ideally with a substantial stenotic component.…”
Section: Atherosclerosismentioning
confidence: 99%